Non-typhoidal Salmonella in food animals in Paraguay: predominant serovars and resistance phenotypes - Irrazábal, Rossana; Iriarte, María V.; Alvarez, Julio (Frontiers in Veterinary Science, 2025)
Surveillance of antimicrobial resistance (AMR) in Salmonella in livestock (poultry, pig, and cattle) is crucial to maintain food safety. Given the lack of information on the situation in livestock in Paraguay, the aim of this study was to determine the most frequent Salmonella serovars in poultry, pig and cattle sampled in slaughterhouses in the country in 2020–22 along with their AMR phenotypes using data from a national pilot program. Out of 1,161 samples collected from slaughtered animals originating from 189 farms nationwide, Salmonella was isolated from 91/384 (23.7%) samples from poultry, 52/390 (13.3%) from pigs and 6/387 (1.6%) from cattle. Seven serovars were identified in poultry, with Heidelberg being the most frequent (82.4% of 91 isolates), while the most frequent serovars in pigs were Panama (48.1%) and Typhimurium (38.5%), and only two serovars (Cerro and Braenderup) were identified in cattle. The proportion of resistant isolates ranged from extremely high (70–83% for nalidixic acid and tetracycline) and high (25–40% for nitrofurantoin and ampicilin) to low-moderate (8–18% for cefixime, cefotaxime, amoxicillin, and trimethoprim- sulfamethoxazole) and very low-low (<6% for ciprofloxacin and gentamicin) depending on the antimicrobial. Up to 23 different resistance profiles were found, ranging from pansusceptible (18/143 isolates) to resistance to 2–7 antimicrobials (median = 2), with the predominant serovars in poultry and swine typically being resistant to ≥3 antimicrobials. These results should be backed-up with genomic analyses to determine the genetic mechanisms involved in the resistance profiles observed in order to support coordinated actions for AMR surveillance and control in the country.